Social Media Preferences in Early Childhood Islamic Education: A Comparative Study of Millennials and Generation Z - Agus Khunaifi; Nasikhin Nasikhin; Agus Sutiyono (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines differences in social media preferences for early childhood Islamic education among Millennial and Generation Z parents. Using a qualitative case study approach, data were collected through structured interviews, participatory observations, and document analysis involving ten participants—five from each generation—in Batang Regency. Findings reveal that Millennials prefer YouTube and Facebook, focusing on structured access to visual educational content such as animated Islamic videos and songs. In contrast, Gen Z actively uses TikTok, Instagram, and educational games, often creating original content or collaborating with online communities to creatively convey Islamic values. For Millennials, social media is a supportive tool to introduce Islamic teachings in a fun, visual way. At the same time, Gen Z uses it to build communities and teach basics like hijaiyah letters. However, a surprising finding is that Gen Z’s usage tends to be irregular, with high frequency and duration, increasing risks of gadget addiction and exposure to negative content. The study contributes to understanding how generational differences shape modern Islamic education strategies via social media. It offers practical insights for parents, educators, and policymakers to develop age-appropriate approaches and establish guidelines for healthy, effective social media use in early Islamic education, ensuring positive engagement while minimizing digital risks.